The Works : Poems Selected from Five Decades - Starbuck, George, 1931-1996 (Book collections on Project MUSE., 2003)
Eighty-one poems spanning the career of the late George Starbuck, widely praised luminary of modern American verse. Starbuck was known in his lifetime and is remembered today as a practitioner of verse remarkable for its pathos, intelligence, and wit. A master of American vernacular, sensitive to the rhythms of everyday speech, Starbuck was also a brilliant lyricist, at once erudite and irreverent. He addressed some of the most profound issues of his day with a playful ingenuity and a virtuosity of talent that Glyn Maxwell, poetry editor of the New Republic, writing in The Oxford Companion to.